Doping composite of polyaniline and reduced graphene oxide with palladium nanoparticles for room-temperature hydrogen-gas sensing. (22nd March 2016) - Zou, Yongjin; Wang, Qingyong; Xiang, Cuili; Tang, Chengying; Chu, Hailiang; Qiu, Shujun; Yan, Erhu; Xu, Fen; Sun, Lixian
Abstract: A composite consisting of polyaniline (PANI) and reduced graphene oxide (rGO) was synthesized by in situ polymerization of the monomer aniline in the presence of rGO under acidic conditions. The PANI–rGO composite substrate was doped with Pd nanoparticles via chemical reduction. The resulting Pd–PANI–rGO nanocomposite was characterized by transmission electron microscopy, scanning electron microscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy before it was utilized to fabricate a hydrogen sensor. Compared with the sensor based on PANI–rGO or PANI, the Pd–PANI–rGO sensor was highly sensitive and selective to hydrogen gas, with fast response time in air at room temperature. The significantly enhanced sensitivity resulted from the faster spill-over effect, dissociation of hydrogen molecules on Pd, and the high surface area of the PANI–GO composite. Based on its improved sensing properties, ease of fabrication, and stable operation, the Pd–PANI–rGO nanocomposite shows promise for high-performance hydrogen-sensing applications. Highlights: In situ polymerization produced composite of polyaniline and reduced graphene oxide. Composite was doped with Pd nanoparticles and used for hydrogen gas sensing. Pd–PANI–rGO ternary nanocomposite shows high sensitivity and selectivity for H2 . The ternary nanocomposite shows fast response and recovery at room temperature.